The Majallah as Codified Fiqh - Danish Naeem (Darulfunun Ilahiyat)
Codification was a widespread phenomenon in 19th-century Europe when the Majallah al-Ahkam al-Adliyyah (Civil Code of the Ottoman Empire, henceforth Majallah) was created. The spirit of the times was such that Europe was heavily under the influence of the French Civil Code. In such a context, the Majallah was envisioned as a means to fill the lacunae in the law as applicable to the judicial system. Accepting the Majallah as a fiqh text transplanted into a codification paradigm raises the problem of whether the imperatives of fiqh accord with those of that paradigm. This article examines the phenomenon of codification and what functions it serves. The article also delves into the history of the Majallah in order to investigate the extent to which it is an expression of a codified paradigm and thereby serves the same functions as the latter. This investigation speaks to the larger imperatives inherent within any effort where Islamic law has been codified.